2009
DOI: 10.1182/blood-2008-08-172726
|View full text |Cite
|
Sign up to set email alerts
|

Active oral regimen for elderly adults with newly diagnosed acute myelogenous leukemia: a preclinical and phase 1 trial of the farnesyltransferase inhibitor tipifarnib (R115777, Zarnestra) combined with etoposide

Abstract: The farnesyltransferase inhibitor tipifarnib exhibits modest activity against acute myelogenous leukemia. To build on these results, we examined the effect of combining tipifarnib with other agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 67 publications
0
59
0
Order By: Relevance
“…Previous studies demonstrated that tipifarnib elicits little cytotoxicity in Jurkat cells over 24 hours. 38 In contrast, after a 48-to 72-hour exposure to tipifarnib, increasing numbers of cells displayed the typical morphologic characteristics of apoptosis ( Figure 1A) as well as phosphatidylserine externalization ( Figure 1B) and DNA fragmentation ( Figure 1C).…”
Section: Tipifarnib Induces Apoptosis Through the Mitochondrial Pathwaymentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies demonstrated that tipifarnib elicits little cytotoxicity in Jurkat cells over 24 hours. 38 In contrast, after a 48-to 72-hour exposure to tipifarnib, increasing numbers of cells displayed the typical morphologic characteristics of apoptosis ( Figure 1A) as well as phosphatidylserine externalization ( Figure 1B) and DNA fragmentation ( Figure 1C).…”
Section: Tipifarnib Induces Apoptosis Through the Mitochondrial Pathwaymentioning
confidence: 94%
“…31,37,38 Briefly, cells were fixed in 3:1 (vol:vol) methanol:acetic acid and dropped onto glass slides. After staining with 1 g/ml Hoechst 33258 in 50% (wt:vol) glycerol containing 100mM Tris-HC1 (pH 7.4 at 21°C), samples were examined on a Zeiss Axioplan microscope using a 63ϫ (NA 1.4) lens, photographed with a Hamamatsu C4742-95 digital camera using QED Image Version 1.7.12 software (QED Imaging), and imported as PICT files into Canvas 8.0.…”
Section: Detection Of Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Whereas many groups have speculated that FTIs induce their effect via ras signaling, [6][7][8] others have suggested alternative pathways by which FTIs exert their anticancer effects. [9][10][11] Marcus et al first reported that FTIs inhibit histone deacetylase 6 expression, resulting in destabilization of the microtubule assembly structure, and impaired cell survival in nonsmall cell lung cancer cell lines. 12 Based on published preclinical data demonstrating that histone deacetylase inhibitors synergize with proteasome inhibition via inhibition of aggresome formation, we sought to determine whether the in vitro synergy we have previously observed using the combination of an FTI with bortezomib was a result of dual blockade of the proteasome and aggresome pathways of protein catabolism.…”
Section: Introductionmentioning
confidence: 99%
“…A number of drugs targeting AML-related genes have been tested for their efficacy in treating AML, including TNF-related apoptosis inducing ligand (TRAIL) and tipifarnib, an inhibitor of farnesyltransferase (FTase), alone or in combination with other anti-leukemia drugs (10,11). Inhibitors of histone deacetylase, proteasome and Bcl-2 antisense oligonucleotides have also been used as targeted drugs in the clinical treatment of AML (12).…”
Section: Introductionmentioning
confidence: 99%